Modelling women`s team line-ups based on effectiveness and quality - Chen, C.; Cao, R.; Ruano, M. Á. G.; Zhou, Y.; Cui, Y. (Journal of Sports Sciences, 2023)
Understanding how different player rotations may impact team performance allows basketball coaches to select effective line-ups for specific tactical scenarios. The study aimed to i) assess how different line-ups or player combinations impact a team`s game performance; ii) explore the variations in line-up utilization among different national women`s basketball teams; and iii) examine how the offensive efficiency of each line-up evolves during the game. Data from 3,387 ball possessions in 23 international women`s basketball games were collected across four major competitions over six years. Offensive and defensive ratings, along with other features, were calculated. Then, a Markov chain model distinguished overperforming and underperforming line-ups of Chinese women`s basketball team, determining long-term probabilities for each rating level. The results indicated that i) the most dominant offensive line-up of the Chinese women`s basketball team, is PG-G-SF-PF-C, while G-G-F-PF-PF had the highest defensive rating; and ii) US and Australian women`s basketball teams favour using line-ups with three guards, while the Chinese women`s basketball team heavily relies on centre players. These results offer valuable insights for coaches regarding the performance of different line-ups in FIBA Female Basketball Competitions, optimizing line-up performance and aiding talent selection and recruitment at the international level.